As Time Goes By: Social and Physical Immobility in the Lives of Undocumented Immigrants in California - Winther, Marianne Søndergaard (Diálogos Latinoamericanos, 2014)
Contrary to popular belief, the current financial crisis has not made the undocumented immigrants residing in the United States leave the country. Accordingly, it continues to be of scholarly interest to investigate how life evolves for these almost 11 million immigrants of predominantly Latin American origin. Focusing mainly on women from Mexico and Central America, this article shows that not only physical but also social immobility is a predominant feature of undocumented, migrant women’s everyday life in the United States. Based on anthropological fieldwork in California and drawing on the work of Pierre Bourdieu, this article focuses on the way time is experienced by undocumented immigrants as they struggle to obtain social mobility while dealing with the consequences of their illegal status.